General public perceptions towards medicines in the state of penang Malaysia - Mahmoud Sa'di Al-Haddad (Archives of Global Professionals, 2012)
Objectives: This study aims to evaluate patients' knowledge, sources of knowledge, and perceptions towards medicines in the state of Penang, Malaysia. Materials and Methods : A cross sectional study design using convenience sampling technique was adopted in this study. A pre-validated questionnaire was developed and distributed to 800 participants in the state of Penang, Malaysia. All data was analysed using SPSS version 16. A p-value of less than 0.05 was considered significant. Results: 700 respondents successfully responded to the survey. One third of the respondents were aware of conventional/modern medicines. Whereas only 3.3% knew what is meant by generic medicines. High proportion of respondents wrongly perceived the quality of medicines to be related to the familiarity with the medicine, frequency of advertisements, price, packaging and country of the manufacturer. In addition, friends, family members, financial status, and previous history, found to play an important role in patients decisions when selecting medicines. Conclusion: Results of this study urge for a national awareness program to the public regarding medicines. Decision makers have to consider these findings since high proportion of the public perceive and consume medicines irrationally.